2015
DOI: 10.1557/mre.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and methane clathrates: Versatility of guest–host compounds for energy harvesting

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Quantum chemistry calculations beyond density functional theory also indicated that the formation of these clathrates is energetically favorable 16 . However, despite the high promise and predicted high stability, experimental synthesis of these inert gas inorganic clathrate has not been reported 17 .…”
mentioning
confidence: 99%
“…Quantum chemistry calculations beyond density functional theory also indicated that the formation of these clathrates is energetically favorable 16 . However, despite the high promise and predicted high stability, experimental synthesis of these inert gas inorganic clathrate has not been reported 17 .…”
mentioning
confidence: 99%
“…2−4 There are two main types of applications for these materials: optoelectronics 5 and batteries. 6 In the first case, the Na x Si 136 type II binary clathrate structure presents semiconducting properties and is able to reach a 1.9 eV quasi-direct bandgap. 7 Furthermore, the material presents the advantage of a direct bandgap as opposed to conventional diamond silicon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the unique features of hydrates are; they are not chemical compounds and are non-stoichiometric crystals [6,7]. Due to no strong chemical bonds exist between the gas and water molecules [8], there is potential of the gas molecules to be released from the water molecules cage [9], which contributes to the flow assurance issues. The three most common gas hydrates structures are structure I (sI), structure II (sII), and structure H (sH), which differs in cage size and physical shape.…”
Section: Introductionmentioning
confidence: 99%